Direct oral anticoagulants versus low-molecular-weight heparin in patients with cancer-associated venous thrombosis: a cost-effectiveness analysis - Wei Kang; Kuan Peng; Vincent K.C. Yan; Daoud Al-Badriyeh; Shing Fung Lee; Hei Hang Edmund Yiu; Yue Wei; Silvia T. H. Li; Xuxiao Ye; Aya El Helali; Ka On Lam; Victor H. F. Lee; et al. (Taylor & Francis Group, 2024)
Background Direct oral anticoagulants (DOACs) have demonstrated clinical benefits and better patient adherence over low-molecular-weight heparin (LMWH) in treating patients with cancer-associated venous thrombosis (CAT). We aimed to compare the cost-effectiveness of DOACs against LMWH in patients with CAT from the perspective of the Hong Kong healthcare system.Methods A Markov state-transition model was performed to estimate the incremental cost-effectiveness ratio (ICER) per quality-adjusted life years (QALYs) for DOACs and LMWH in a hypothetical cohort of 10,000 patients with CAT over a 5-year lifetime horizon. The model was primarily based on the health states of no event, recurrent venous thromboembolism, bleeding, and death. Transition probabilities, relative risks, and utilities were derived from the literature. Resource cost data were obtained from the Hong Kong Hospital Authority. Deterministic and probabilistic sensitivity analyses tested the robustness of the results.Results Relative to LMWH, DOACs were associated with increased QALYs (1.52 versus 1.50) at a lower medical cost of USD 2,232 versus 8,224 in five years. The cost of LMWH was the main contributor to the outcome. Out of 10,000 simulated cases, DOACs were dominant in 15.8% and cost-effective in 42.1%, at the willingness-to-pay threshold of USD 148,392 per additional QALY.Conclusions DOACs were associated with greater QALY improvements and lower overall costs compared to LMWH. Accounting for uncertainty, DOACs were between cost-effective and dominant in 57.9% of cases. DOACs are a cost-effective alternative to LMWH in the management of CAT in Hong Kong.